The Privatization of Hope : Ernst Bloch and the Future of Utopia, SIC 8 - Žižek, Slavoj; Thompson, Peter, 1960 July 22- (Book collections on Project MUSE., 2013)
The concept of hope is central to the work of the German philosopher Ernst Bloch (1885-1977), especially in his magnum opus, 'The Principle of Hope' (1959). The 'speculative materialism' that he first developed in the 1930s asserts a commitment to humanity's potential that continued through his later work. In this book, leading thinkers in utopian studies explore the insights that Bloch's ideas provide in understanding the present.